The ambivalent moderation of Hindu nationalism in India - Mitra, Subrata Kumar (Australian journal of political science, 2013)
Despite regular participation in national and regional elections and occupation of office both at the centre and in the regional governments, the Hindu nationalist Bharatiya Janata Party (BJP) has not acquired the aura of moderation. It has not achieved acceptance into the party system of India in a manner that would make it comparable to Christian Democratic parties in Europe. This appears puzzling in the light of Downs’ moderation thesis, which suggests that regular participation in free, fair and competitive elections transforms extremist parties to moderates as they converge towards the median voter. The article approaches this puzzling counterfactual in intra-system comparison by drawing on the case of Sikh nationalism. With a focus on BJP, the article presents an analysis of party competition, party programs, policies and public opinion data on issue positions and the social base of the party. In conclusion, three general enabling conditions are identified that help explain the deviant case of the ambivalent moderation of the BJP.印度人民党虽然参加全国和地方选举，虽然在中央和地方政府中任职，但并没有因此就有稳健克制的样子。它没有能够像欧洲的基督教民主党那样被纳入印度的政党体系。这就成为汤恩的克制理论解释不了的谜团，按汤氏的理论，正常参加自由、公正而竞争性的选举，会使极端主义政党变得稳健克制，向一般投票者趋近。本文通过系统内比较，以民族主义的锡克教为例，破解了这个谜团。作者聚焦印度人民党，分析了政党竞争，政党计划、政策以及关于某些话题立场的舆论资料、还有政党的社会基础。作者发现三种情形能够一般性地解释印度人民党的偏激不稳健。
Gesehen am 25.05.2021